Investigation of memory responses following Plasmodium chabaudi AS infection in mice distinct in susceptibility to clinical malaria - Jiraprapa Wipasa (2018)
Plasmodium chabaudi chabaudi AS blood stage infection results in various degrees of clinical symptoms to malaria depending on the mouse strain. This study aimed to investigate the development of memory responses in susceptible A/J and resistant C57BL/6 mice which differ in the degree of susceptibility to clinical malaria following P. chabaudi AS infection. A rapid increase of activated cells (CD25+, CD44high, and CD62Llow) and production of both interferon-γ and interleukin-4 was found in spleens of both malaria-infected mouse strains. After the parasitemia had been cleared, these activated cells were converted to their resting phenotypes. Although exhibiting susceptible phenotype and having lower magnitude of cellular changes during primary infection, susceptible A/J mice that had been exposed to malaria parasites and drug-cured were able to generate protective immunity capable of control parasite growth following reinfection to the same level as C57BL/6 mice. This may be due to the capability of susceptible mice to produce parasite-specific antibodies, in particular of the IgG2a and IgG3 isotypes. The results from this study may provide more insights useful for the development of vaccines against malaria. © 2009 Springer-Verlag.